Analytical and mineralogical study of a Ghana manganese ore: Quantification of Mn speciation and effect of mechanical activation. (November 2016) - He, Hongping; Cao, Jianglin; Duan, Ning
Abstract: In-depth understanding of the manganese ore would be beneficial to make the best use more environmental-friendly. A Ghana manganese ore before/after mechanical activation (MA) was therefore extensively characterized in our investigation. Surface Mn 4+ (35.5%), Mn 3+ (35.9%), Mn 2+ (28.6%) were detected by XPS, though XRD only revealed the presence of Mn 2+ -containing minerals. Thermal decomposition curve of manganese ore obtained by TG-DSC was divided into four stages from 373.15 K to 1273.15 K, which were quite consistent with the pattern of generated gases obtained by TG-FTIR and the theoretical thermodynamics analysis of the incorporated components involving Δ G T θ and K p θ . Mn species distribution showed no difference for manganese ores before/after MA, but quantitative analysis showed the decrease of residual Mn content (cannot be extracted effectively by acid, from about 12% to 1%), and thereby the increased contents of other four Mn species (exchangeables, carbonates, oxides, organics), which was suggested to be correlated with the dissociation of Mn-containing flocs and SiO2 particles witnessed by SEM-EDS. It was also found that MA could obviously promote the Mn dissolution kinetics in acid condition, though the dissolution of manganese ore before/after MA were both diffusion controlled. This investigation gives benignant inspiration for the resource utilization of manganese ore, taking the increasingly severer situation of Mn resource supply into consideration. Highlights: Extensive characterization was conducted to understand the manganese ore. TG-DSC curve was quite consistent with that of TG-FTIR and thermodynamics analysis. It was found that mechanical activation could change the distribution of Mn speciation. Mn speciation distribution variation was correlated with the dissociation of Mn-containing flocs and SiO2 particles.